Politic psychology in Mexico: advance and prospective - Rosado Vázquez , Gilbert Azael (Consorcio de Universidades Mexicanas A.C., 2018)
The aim of this article is to outline the historical development of Political Psychology worldwide, in Latin America, and Mexico and to present its evolution from origins to recent advancements. It likewise provides a brief exploration of the fundamental theoretical concepts to allow for a better understanding of the relationship between the fields. Political Psychology has opened research avenues that lead to the study of the individual and the collective to allow for direct identification of the causes of political behavior. The article specifically focuses on Mexico and describes advancements through a review of specialized publications to analyze the principle topics of the previous decades as well as the pending agenda and future directions for research in the country. Results were obtained from databases, magazines, and Mexican national universities, etc. This is a reflection of the bibliographic material currently available, which allows for a detailed analysis of the congruence between developments in the academic area and scientific production with the ultimate goal of encouraging growth.